Osimertinib-Induced Cutaneous Vasculitis Responsive to Low-Dose Dapsone Without Interruption of Anticancer Therapy: A Case Report and Review of the Literature - Christopher Iriarte, MD; Jonathan H. Young, MD, PhD; Michael S. Rabin, MD; Nicole R. LeBoeuf, MD, MPH (JTO Clinical and Research Reports, 2022)
A 45-year-old woman with a history of lung adenocarcinoma treated with osimertinib developed purpuric plaques and vesicles on the lower extremities after 5 months of therapy. Skin biopsy revealed leukocytoclastic vasculitis (LCV). A workup for systemic involvement was unremarkable. The patient was treated with oral dapsone while continuing osimertinib without interruption. Skin lesions cleared within 2 weeks of therapy with no recurrence after titrating off dapsone. To the best of our knowledge, this is the first reported case of LCV induced by a small-molecule EGFR inhibitor in which therapy was not interrupted. This is also the first reported case treated with dapsone rather than systemic corticosteroids. We suggest consideration of dapsone to treat skin-limited LCV induced by EGFR inhibitors in patients with lung cancer without features of systemic vasculitis. In addition, this case highlights that it may not be necessary to stop EGFR inhibitor therapy in the absence of severe features such as ulceration, bullae, necrosis, or severe pain. Dapsone is an effective targeted therapy for cutaneous LCV that does not globally impair the immune system and may allow for uninterrupted treatment of the underlying malignancy.